Protein structure optimization using improved simulated annealing algorithm on a three-dimensional AB off-lattice model. (April 2020) - Zhang, Lizhong; Ma, He; Qian, Wei; Li, Haiyan
Graphical abstract: Highlights: The improved algorithm outperforms those reported algorithms on the testing of artificial protein sequences. The improved algorithm can obtain folding conformations with Cα -RMSD less than 3.0 Å from PDB structures for real proteins. Cα space-filling model can provide dynamic change of protein folding conformation at atomic level. Abstract: This paper proposed an improved simulated annealing (ISA) algorithm for protein structure optimization based on a three-dimensional AB off-lattice model. In the algorithm, we provided a general formula used for producing initial solution, and designed a multivariable disturbance term, relating to the parameters of simulated annealing and a tuned constant, to generate neighborhood solution. To avoid missing optimal solution, storage operation was performed in searching process. We applied the algorithm to test artificial protein sequences from literature and constructed a benchmark dataset consisting of 10 real protein sequences from the Protein Data Bank (PDB). Otherwise, we generated Cα space-filling model to represent protein folding conformation. The results indicate our algorithm outperforms the five methods before in searching lower energies of artificial protein sequences. In the testing on real proteins, our method can achieve the energy conformations with Cα -RMSD less than 3.0 Å from the PDB structures. Moreover, Cα space-filling model may simulate dynamic change of protein folding conformation at atomic level.